2017
DOI: 10.2196/mhealth.6239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of a Fitbit Physical Activity Monitor on the Exercise Practices of Emergency Medicine Residents: A Pilot Study

Abstract: BackgroundTargeted interventions have improved physical activity and wellness of medical residents. However, no exercise interventions have focused on emergency medicine residents.ObjectiveThis study aimed to measure the effectiveness of a wearable device for tracking physical activity on the exercise habits and wellness of this population, while also measuring barriers to adoption and continued use.MethodsThis pre-post cohort study enrolled 30 emergency medicine residents. Study duration was 6 months. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 40 publications
4
49
1
Order By: Relevance
“…According to the qualitative ndings, this was more pronounced for o cers and staff who were less active at the beginning of the study, and lacking in intrinsic motivation. Similar ndings have been reported in previous mHealth studies, where less active subgroups have shown the largest increases in PA (46,47). This nding is encouraging in that less active individuals are likely to realise the greatest health gains from increasing their PA levels (48).…”
Section: Discussionsupporting
confidence: 89%
“…According to the qualitative ndings, this was more pronounced for o cers and staff who were less active at the beginning of the study, and lacking in intrinsic motivation. Similar ndings have been reported in previous mHealth studies, where less active subgroups have shown the largest increases in PA (46,47). This nding is encouraging in that less active individuals are likely to realise the greatest health gains from increasing their PA levels (48).…”
Section: Discussionsupporting
confidence: 89%
“…Even among those who proceeded to use the belt-worn LUMOback, usage was low. Workplace studies evaluating trackers clipped on to the hip or shoe [ 12 , 13 , 27 ], worn on the wrist [ 14 , 30 ], or worn in a range of hip, wrist, and chest locations [ 31 ] have reported usage ranging from a mean use of 79% days across 6 weeks of intervention [ 12 ] to a mean use of approximately 69% days across 3 months of intervention [ 27 ], and 15% to upward of 89% of participants still using their tracker after 2 months [ 13 , 14 , 30 , 31 ]. All studies reporting high usage incorporated monetary incentives [ 13 , 27 ] or text message/email prompts [ 12 ] to encourage usage.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies utilizing activity trackers use tracker output as outcomes, and recording time is mostly limited to the intervention period [8]. Exceptions include Schrager et al [17] who used a Fitbit Flex to collect PA over one month (secondary outcomes), Carmichael et al [18] who used a Garmin Vivo t 3 to collect PA (primary outcome) for up to one month of follow-up, and Patel et al [19] who used a Fitbit Flex in a 12-week intervention, with 12-weeks of follow-up. Although long time follow-ups with consumerbased activity trackers are uncommon, such studies are likely to increase in frequency going forward.…”
Section: Introductionmentioning
confidence: 99%